Acceptability and usability of self-collected sampling for HPV testing among African American women living in the Mississippi Delta - Scarinci, Isabel C. (2013)
BACKGROUND: HPV DNA testing has been shown to be an effective approach to cervical cancer screening, and self-collection sampling for HPV testing could be a potential alternative to Pap test, provided that women who tested positive by any method get timely follow-up and care. This feasibility study examined acceptability and usability of self-collected sampling for HPV testing among African American (AA) women in the Mississippi Delta in order to inform the development of interventions to promote cervical cancer screening in this population. METHODS: The study consisted of two phases. Phase I consisted of eight focus groups (N=87) with AA women to explore knowledge, attitudes, and beliefs about cervical cancer and HPV infection as well as acceptability of self-collected sampling for HPV testing. In Phase II, we examined the usability of this technology through one discussion group (N=9). The Health Belief Model guided data collection and analysis. RESULTS: Although participants perceived themselves as susceptible to cervical cancer and acknowledged its severity, there was a lack of knowledge of the link between HPV and cervical cancer, and they expressed a number of misconceptions. The most frequent barriers to screening included embarrassment, discomfort, and fear of the results. Women in both phases were receptive to self-collection sampling for HPV testing. All participants in the usability phase expressed that self-collection was easy and they did not experience any difficulties. CONCLUSION: Self-collection for HPV testing is an acceptable and feasible method among AA women in the Mississippi Delta to complement current cytology cervical cancer screening programs.